The Storytelling and Improvement of Language and Social Skills in Autism Children - Debi Sambak; Tuti Seniwati; Akbar Harisa (Faculty of Nursing, Universitas Hasanuddin, 2021)
Introduction: In Indonesia, the number of children who suffer from autism identified around 6,900 children in every year. The autism characterised by a communication disorder due to the delay in speech, that affect the children were incomprehensible of language skill and also interference with interaction. Stimulation is an important therapy in order to maximize all the potential skills of the children. A form of stimulation which possibly applies is a story telling therapy, that therapy is given in an early age. This study aims to describe the level of language and social interaction skills among children with autis who were attending a story telling stimulation therapy class in the center of therapy Pelita Mandiri Makassar. Method: This study applied descriptive analytic research design with a cross sectional approach. There were 30 children with autis recruited in this study. Results: The results of this study shows that children who attend story telling stimulation therapy class have signifincantly improvement in both language and social interaction skills particularly in 21.9% of participants. The children who able to speak with their own language and understood by others (76.7%), children who was able to mention the sounds (70%). Conclusion: Story telling stimulation therapy program has potential benefit on language and social interaction skills improvement in children with autism.